An experimental study on the flow and heat transfer of an impinging synthetic jet. (December 2019) - Xu, Yang; Moon, Chanhee; Wang, Jin-Jun; Penyazkov, Oleg G.; Kim, Kyung Chun
Graphical abstract: Highlights: Thermographic phosphor (TPs) was first used to investigate heat transfer of an impinging synthetic jet. A link was built between the flow structure and the cooling performance. Wall temperature's influence was reflected in the strength of the wall shear layer. Effect of the orifice-to-wall distance was manifested in the coherence of impinging vortex rings. Penetration of the wall shear layer played a vital role in the cooling performance of an impinging synthetic jet. Abstract: This study experimentally investigated the combined effects of the wall temperature ( Tw 0 ) and the orifice-to-wall distance ( H / D ) on the flow and heat transfer characteristics of an impinging synthetic jet. Thermographic phosphor thermometry (TPT) was used to measure the wall surface temperature, and the quantitative flow velocity was obtained using time-resolved particle image velocimetry (PIV). A cavity-diaphragm actuator was employed to generate a round synthetic jet to impinge onto a heated wall that was coated with Mg4 FGeO6 :Mn (MFG) for use as a temperature sensor. Three orifice-to-wall distances ( H / D  = 10, 15, and 20) and three wall temperatures ( Tw 0  = 60 °C, 90 °C, and 120 °C) were tested for comparison, whereas the the operating conditions of the incident synthetic jet were kept constant. It was found that the maximum temperature drop at the stagnation point could reach approximately 50°C although the orifice-to-wall distance was relatively large in this study, which indicated a good cooling performance of the synthetic jet. The penetration of the wall shear layer played an important role on the cooling performance of the impinging synthetic jet. For a heated wall with high Tw 0, the enhanced buoyancy and thermal boundary layer resulted in the formation of a strong wall shear layer, which was more difficult for the impinging synthetic jet to affect or penetrate. For a large H / D, the vortex rings of the synthetic jet lose coherence completely before impacting the wall. Thus, they have no ability to penetrate the wall's shear layer to interact with it directly. As a result, the cooling performance of the impinging synthetic jet gradually decreased as both Tw 0 and H / D increased. In particular, the maximum cooling effect by the synthetic jet impingement can achieve 64% of the theoretical maximum.